Remediation of an acidic mine spoil: Miscanthus biochar and lime amendment affects metal availability, plant growth, and soil enzyme activity. (August 2018) - Novak, Jeffrey M.; Ippolito, James A.; Ducey, Thomas F.; Watts, Donald W.; Spokas, Kurt A.; Trippe, Kristin M.; Sigua, Gilbert C.; Johnson, Mark G.
Abstract: Biochar may be a tool for mine spoil remediation; however, its mechanisms for achieving this goal remain unclear. In this study, Miscanthus (Miscanthus giganteus) biochar was evaluated for its ability to reclaim acidic mine spoils (pH < 3) through reducing metal availability, improving soil microbial enzymatic activity, and initial growth of grass seedlings. Biochar was applied at 0, 1, 2.5 and 5% (w/w) along with lime/no lime and fertilizer additions. Blue Wildrye ( Elymus glaucus cv. 'Elkton') was planted and later the shoots and roots were collected and metal concentrations determined. Afterwards, each pot was leached with deionized water, and the leachate analyzed for pH, electrical conductivity (EC), dissolved organic carbon (DOC) and soluble metal concentrations. After drying, the spoil was extracted with 0.01 M CaCl2 and Mehlich 3 (M3) to determine extractable Al, Cu, and Zn concentrations. Additionally, microbial activity was measured using a fluorescent β-glucosidase and N -acetyl-β-d -glucosaminidase assay. Spoil treated with lime and biochar had significantly greater pH and EC values. Significantly greater β-glucosidase activity occurred only in the 5% biochar plus lime treatment, while N -acetyl-β-d -glucosaminidase activities were not altered. Metal concentrations in rye shoot and roots were mixed. Lime additions significantly reduced extractable metal concentrations. Increasing biochar rates alone significantly reduced leachate DOC concentrations, and subsequently reduced leachable metal concentrations. Surprisingly, miscanthus biochar, by itself, was limited at mitigation, but when combined with lime, the combination was capable of further reducing extractable metal concentrations and improving β-glucosidase enzyme activity. Highlights: Blue Wildrye shoot and root growth was improved after lime treatment of spoil. Miscanthus biochar had minimal impact on reducing extractable metal concentrations. Lime increased mine spoil pH and reduced extractable metal concentrations. Water leachates were lower in dissolved metals after lime and biochar additions. Microbial enzymatic activity was influenced only at highest biochar and lime application.